Life cycle assessment of three types of hydrogen production methods using solar energy. (8th April 2022) - Zhang, Jinxu; Ling, Bo; He, Yong; Zhu, Yanqun; Wang, Zhihua
Abstract: A comprehensive life cycle assessment (LCA) is carried out for three methods of hydrogen production by solar energy: hydrogen production by PEM water electrolysis coupling photothermal power generation, hydrogen production by PEM water electrolysis coupling photovoltaic power generation, and hydrogen production by thermochemical water splitting method using S–I cycle coupling solar photothermal technology. The assessment also contains an evaluation of four environmental factors which are global warming potential, acidification potential, ozone depletion potential, and nutrient enrichment potential. After conducting a quantitative analysis of all three methods with environmental factors being considered, a conclusion has been drawn: The global warming potential and the acidification potential of the thermochemical water splitting by S–I cycle coupling solar photothermal technology are 1.02 kg CO2 -eq and 6.56E-3 kg SO2 -eq. And this method has significant advantages in the environmental impact of the whole ecosystem. Highlights: Photothermal technology coupling hydrogen production by S–I cycle has the lowest environmental impact. Optimal heat source for PEM water electrolysis is photovoltaic power generation. Reducing the pollution in the construction of plant can reduce the pollution of the whole hydrogen production system. Increasing the lifetime of the system can reduce the environmental impact of hydrogen production.